Marketing Mix that affects The Decision to Buy One Tambon One Product of Consumers in The Kanchanaburi Municipality, Mueang District, Kanchanaburi - Kitiyanan, Sanchai (Journal of Management Science Nakhon Pathom Rajabhat University, 2024)
This research aims. 1) study the personal factors that affect the decision to buy one Tambon Oneproduct of consumers. 2) Study the Marketing Mix that affect the decision to buy one Tambon Oneproduct of consumers in the Kanchanaburi municipality, Mueang District, Kanchanaburi Province. The sample used in this study was a group of 315 members using Convenient Sampling. The instrument used in the research was a questionnaire. The rating scale with 5 levels has content validity between 0.67-1.00 and the whole reliability of 0.96. The statistics used for data analysis are percentage, mean and standard deviation and correlation Pearson (Pearson’s Product Moment correlation) test Multiple regression analysis with the enter method. The statistical significance level was set at 0.05. The study found that 1) personal factors (gender, age, education and income) significantly predicted the decision to buy one Tambon Oneproduct of consumers in the Kanchanaburi municipality, Mueang District, Kanchanaburi Province. There were not differences. 2) Marketing mix predicted the decision to buy one Tambon One product of consumers in the Kanchanaburi municipality, Mueang District, Kanchanaburi Province That affect the decision of consumer significantly at 0.05. When split into sides, it was found that Consumers will pay attention to the decision to buy OTOP products in terms of price. distribution channels in terms of marketing promotion and The process aspect was significantly different at 0.05. As for the product aspect, the person aspect and the physical aspect Affecting the decision to buy one Tambon One Product in Kanchanaburi Municipality, Muang District, Kanchanaburi Province. No difference. Article history: Received 20 July 2023 Revised 8 October 2023 Accepted 10 October 2023 SIMILARITY INDEX = 17.38 %